2009
DOI: 10.1002/mds.22727
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of SCA2 and SCA3/MJD repeats in Parkinson's disease in mainland China: Genetic, clinical, and positron emission tomography findings

Abstract: Abstract:We report the neuropathological findings in a patient with Parkinson's disease (PD) associated with Basque R1441G-LRRK2/dardarin mutation. The patient was a man with disease onset at 68 years of age, with unilateral rest tremor; the Parkinsonism was well controlled with medication for 15 years. He died at the age of 86, after 18 years of evolution. The neuropathological examination disclosed mild neuronal loss in the substantia nigra pars compacta without a-synuclein, tau, LRRK2, or ubiquitin cytoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 14 publications
1
25
1
4
Order By: Relevance
“…Sequence analyses suggested that the normal allele contained two CAA interruptions and displayed a configuration of (CAG) 8 CAA(CAG) 4 CAA(CAG) 8 , while the expanded alleles only contained a reserved 3’-CAA interruption and displayed a configuration as (CAG) n CAA(CAG) 8 . Two patients had participated in a previous study, and had been examined with [ 11 C]-CFT (2-b-carbomethoxy-3b-(4-fluorophenyl)tropane) positron emission tomography (PET) showing bilateral decrement of 11 C-CFT uptake in the stratum [16]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sequence analyses suggested that the normal allele contained two CAA interruptions and displayed a configuration of (CAG) 8 CAA(CAG) 4 CAA(CAG) 8 , while the expanded alleles only contained a reserved 3’-CAA interruption and displayed a configuration as (CAG) n CAA(CAG) 8 . Two patients had participated in a previous study, and had been examined with [ 11 C]-CFT (2-b-carbomethoxy-3b-(4-fluorophenyl)tropane) positron emission tomography (PET) showing bilateral decrement of 11 C-CFT uptake in the stratum [16]. …”
Section: Methodsmentioning
confidence: 99%
“…Additionally, PET results indicated that the patients had dopaminergic deficits [16]. Therefore, it is logical to consider that these asymptomatic SCA2 mutation carriers were at the preclinical stage of parkinsonism and provide a good dataset to investigate neural modulations at preclinical and clinical stage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the clinical syndromes from the varied mutations may be strikingly similar to each other [2, 3]. Previous study [46] suggested that the CAG repeats mutation in SCA2 or SCA3/Machado-Joseph disease (MJD) may be associated with Parkinsonism. A recent study [7] showed a common molecular mechanism between SCA3/MJD and ALS due to the similar ubiquitination and degradation of ataxia-3 and SOD.…”
Section: Introductionsmentioning
confidence: 99%
“…Previous clinical and pathologic findings emphasize the need to evaluate the significance of polyglutamine repeat expansions of these genes in PD worldwide. [4][5][6][7][8][9] Most studies performed to date, including this study, are biased by case selection at specialist movement disorders clinics. However, to get a better estimate of the frequency of repeat expansions in such a setting, their relative contribution to disease worldwide, we performed a large multicenter study with members of the Genetic Epidemiology of Parkinson's Disease (GEO-PD) Consortium.…”
mentioning
confidence: 99%